“The virus will not have a chance against us” Transitivity Analysis on Donald Trump’s 2020 Coronavirus Speech - Lukka, Sara (My University, 2021)
A Transitivity Analysis on Donald Trump’s 2020 Coronavirus Speech. The aim of this thesis was to examine the ideological implications and the representations of the America. Furthermore, this thesis examined the relations between the America and other areas. In addition, this thesis examined how President Trump’s speech emphasizes Americanism ideology. The material for this thesis was gathered from the official website of White House government. The material consisted of Trumps speech which was presented in March 2020 after the coronavirus began to spread in the world and when Worlds Health Organization (WHO) declared COVID-19 as a pandemic. The research was conducted with the help of Halliday’s Systemic Functional Grammar and van Dijk’s methodology (ideology categories and ideological square) from the point of view of Critical Discourse analysis. The results highlighted that the speech wanted to emphasize the good things made by the Americans while weaking the bad things. The bad things done by other countries were highlighted. Americanism ideology was an important influencer on how Trump represents the current situation in his speech. The results revealed that a single speech can consist of various of factors such as power use, discrimination, or ideologies.

Transitiivisuusanalyysi Donald Trumpin vuoden 2020 koronaviruspuheesta. Tutkimuksen tavoitteena oli tutkia Amerikan ideologisia vaikutuksia ja representaatioita. Lisäksi tässä tutkimuksessa tarkasteltiin Amerikan ja muiden alueiden välisiä suhteita. Näiden tekijöiden lisäksi tässä tutkimuksessa tarkasteltiin, kuinka presidentti Trumpin puhe korostaa amerikkalaisuuden ideologiaa. Tutkimuksen aineisto kerättiin Valkoisen talon virallisilta verkkosivuiltas. Aineisto koostui maaliskuussa 2020 esitellystä Trumpin puheesta, jossa käsiteltiin koronaviruksen leviämistä maailmassa, maailman terveysjärjestö (WHO) julistaessa COVID-19:n pandemiaksi. Tutkimuksen aineistoa käsiteltiin Hallidayn transitiivisuusteorian kriittisen diskurssintutkimuksen sekä van Dijkin ideologian määritelmiä hyödyntäen. Tulokset paljastivat, että puheella haluttiin korostaa amerikkalaisten tekemiä hyviä tekoja ja samalla heikentää huonoina koettuja tekoja. Muiden maiden tekemiä huonoja tekoja korostettiin ja hyviä tekoja heikennettiin. Amerikkalainen ideologia vaikutti merkittävästi siihen, miten Trump kuvailee puheessaan koronaviruksen leviämistä. Tulokset paljastivat lisäksi sen että yksi puhe voi koostua useista erilaisista tekijöistä, kuten voimankäytöstä, syrjinnästä tai ideologioista.
Keywords: discourse, politics, speech, qualitative research